PENGARUH TANGGUNGJAWAB SOSIAL PERUSAHAAN TERHADAP KINERJA KEUANGAN DENGAN TATA KELOLA PERUSAHAAN SEBAGAI VARIABEL MODERASI - Agnes Janiartini; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2020)
The theoretical and empirical relationships between corporate social responsibility (CSR) and corporate financial performance are not without controversy. Yet, CSR activities are increasingly undertaken by a large number of firms, not only indeveloped countries but also inemerging countries. This paper aims to investigate the moderating effect of different aspects of corporate governance, which are foreign and state ownership, board size and board independence, on the relation ship between CSR and financial performance. This study uses secondary data from financial statements of manufacturing, agriculture, mining, wholesale and retail trade companies listed on Indonesia Stock Exchange in 2017-2018. The sampling method used is purposive sampling. The sample consists of 231 financial reports from 159 companies that listed in Indonesia Stock Exchange period 2017-2018. The analysis method that was used in this study was linear regression analysis. Before being conducted by regression test, it was examined by using classical assumption test are the normality, heterocedasticity, multicollinearity, and autocorrelation tests. Ordinary least squares regression results show that CSR activities affect the financial performance of firms positively. Furthermore, corporate governance features like foreign ownership, stateownership,board size and board independence strengthen the positive relationship between CSR and financial performance